(untitled) (Journal of the Bangladesh Agricultural University, 2026)
Freshwater zooplankton communities include diverse rotifer taxa, yet species-level documentation in Bangladesh remains limited. The present study reports the occurrence of Anuraeopsis coelata (Gosse, 1851) and Lecane ludwigii (Eckstein, 1883) from freshwater habitats within the University of Chittagong campus, Bangladesh. Zooplankton samples were collected between November 2023 and April 2024 and examined under light microscopy. Species identification was carried out using diagnostic morphological characters following established taxonomic keys, supported by morphometric measurements obtained from calibrated photomicrographs. Lorica length and width were measured for A. coelata, while total body length and maximum body width were recorded for L. ludwigii. The recorded measurements fall within the diagnostic ranges reported in previous studies, supporting the identification of the examined specimens. These observations represent the first morphologically confirmed records of both species from Bangladesh and provide baseline taxonomic information for future studies of freshwater rotifer diversity in the region. Further investigations incorporating broader sampling and molecular approaches may help refine species identification and improve understanding of rotifer diversity in Bangladeshi freshwater ecosystems. J Bangladesh Agril Univ 24(1): 49–56, 2026